Coated nickel cobalt lithium manganese oxide positive electrode material and preparation method thereof and battery
By forming an organic-inorganic coating layer of polyamide porous film and an inorganic coating agent on the surface of the nickel-cobalt manganese oxide positive electrode material, the problem of attenuation of the cyclic capacity and poor structural stability of the material under high voltage conditions is solved, and the cycling performance and corrosion resistance of the battery are significantly improved.
Patent Information
- Application Number
- CN202211475748.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-11-23
AI Technical Summary
Nickel-cobalt lithium manganate positive electrode material has fast cycling capacity decays, poor structural stability under high voltage conditions, poor interfacial stability of the coating layer and low electronic conductivity, which affects the cycling performance of the battery.
By spraying the polyamide solution on the surface of the prefabricated matrix, removing the solvent, the polyamide precipitates out to form a porous film, and modifying the conductive zinc oxide whiskers with inorganic coating agents such as silane to form an organic-inorganic coating layer to improve the conductivity and structural stability of the material.
The cycling performance of the nickel-cobalt lithium manganate cathode material under high voltage is improved, structural stability is enhanced, and it can resist electrolyte corrosion, avoid direct contact between the positive electrode material and the electrolyte, and promote repeated disengagement and embedding of lithium.
Smart Images

Figure CN115763745B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a coated nickel cobalt lithium manganese oxide positive electrode material, a preparation method thereof, and a battery. Background Art
[0002] Lithium Nickel Cobalt Manganese Oxide (LiNi x Co y Mn z O2, where 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1) is a lithium-ion battery positive electrode material with excellent electrochemical properties. The lithium-ion battery prepared using it has the advantages of high specific capacity, high energy density, low self-discharge, no memory effect and strong cycle stability.
[0003] However, there are still some problems with lithium nickel cobalt manganese oxide materials, such as the electrolyte has a certain corrosive effect on the electrode material, which causes the capacity of the material to decay and affects the cycle stability of the material. Therefore, the modification of the positive electrode material has become an important means to improve the electrochemical performance of the material, among which coating is the simplest and most effective method. The presence of the coating layer can maintain its own surface structure stability, avoid direct contact between the active material and the electrolyte, and inhibit the dissolution of transition metal elements in the material under high potential conditions, thereby improving the capacity retention rate of the positive electrode material.
[0004] However, the presence of the coating layer results in poor interface stability, low electronic conductivity, and still poor cycle performance of the prepared battery. Summary of the invention
[0005] The object of the present invention is to provide a coated nickel cobalt lithium manganese oxide positive electrode material and a preparation method thereof and a battery. The preparation method of the present invention can produce a coated nickel cobalt lithium manganese oxide positive electrode material with better cycle performance.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a method for preparing a coated nickel cobalt lithium manganese oxide positive electrode material, comprising:
[0008] Mixing a substrate with an inorganic coating agent to obtain a prefabricated substrate, wherein the substrate includes secondary spherical lithium nickel cobalt manganese oxide;
[0009] Mixing polyamide and a first solvent, dissolving, and then mixing with a second solvent to obtain a polyamide solution, wherein the solubility of the polyamide in the first solvent is greater than the solubility of the polyamide in the second solvent;
[0010] The polyamide solution is sprayed on the surface of the prefabricated substrate, the solvent is removed, the substrate is washed, centrifuged and dried to obtain a coated nickel cobalt manganese oxide lithium positive electrode material.
[0011] In an optional embodiment, at least one of the first solvent and the second solvent is selected from at least one of formamide, glycerol and ethylene glycol.
[0012] In an optional embodiment, the ratio of the mass of the polyamide to the total mass of the first solvent and the second solvent is 1%-5%; the mass ratio of the first solvent to the second solvent is (3-8):(4-6).
[0013] In an alternative embodiment, removing the solvent comprises heat treatment, and the temperature of the heat treatment is 120-180°C.
[0014] In an optional embodiment, the inorganic coating agent is nanoparticles having conductive properties; the nanoparticles having conductive properties include silane-modified conductive zinc oxide whiskers.
[0015] In an alternative embodiment, the inorganic coating agent accounts for 1% to 10% of the weight of the substrate.
[0016] In an optional embodiment, the polyamide is a polyamide oligomer and has a weight average molecular weight Mw of 1000-50000 g / mol.
[0017] In an optional embodiment, the mass ratio of the polyamide solution to the prefabricated matrix is 2:(2-4).
[0018] In a second aspect, the present invention provides a positive electrode material, which is prepared by the preparation method of the coated nickel cobalt lithium manganese oxide positive electrode material of any one of the aforementioned embodiments.
[0019] In a third aspect, the present invention provides a battery comprising the positive electrode material of the aforementioned embodiment.
[0020] The present invention has the following beneficial effects:
[0021] The method for preparing the coated nickel cobalt lithium manganese oxide positive electrode material provided in the embodiment of the present invention allows polyamide to precipitate to form a porous film attached to the surface of the nickel cobalt lithium manganese oxide substrate after the solvent evaporates, that is, a polyamide porous film can be formed to coat the nickel cobalt lithium manganese oxide substrate, so as to improve the cycle performance of the prepared positive electrode material under high voltage, and enhance the structural stability of the positive electrode material, and be able to resist electrolyte corrosion under high voltage. Moreover, during the preparation, the addition of an inorganic coating agent improves a certain conductivity, and cooperates with the polyamide coating layer to further improve the conductivity of the material.
[0022] The positive electrode material provided in the embodiment of the present invention is prepared by the aforementioned method for preparing the coated nickel cobalt lithium manganese oxide positive electrode material. The organic-inorganic coating layer formed on its surface improves the cycle performance of the material under high voltage. The nickel cobalt lithium manganese oxide matrix is coated with the formed polyamide porous membrane, which can also resist electrolyte corrosion under high voltage conditions, avoid direct contact between the positive electrode material and the electrolyte, and is conducive to the repeated removal and embedding of lithium.
[0023] The battery provided by the embodiment of the present invention includes the aforementioned positive electrode material, which has enhanced cycle performance under high voltage, and the positive electrode material is resistant to electrolyte corrosion under high voltage conditions, avoiding direct contact between the positive electrode material and the electrolyte, and is conducive to repeated extraction and embedding of lithium. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 This is a SEM image of the nickel cobalt manganese oxide positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0027] Lithium nickel cobalt manganese oxide materials have properties such as high voltage platform and high discharge capacity, and are widely used in the lithium battery field.
[0028] Lithium Nickel Cobalt Manganese Oxide (LiNi x Co y Mn z O2, where 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1) is a lithium-ion battery positive electrode material with excellent electrochemical properties. The lithium-ion battery prepared using it has the advantages of high specific capacity, high energy density, low self-discharge, no memory effect and strong cycle stability. However, the cycle capacity of nickel cobalt manganese oxide positive electrode material decays quickly under high voltage conditions and has poor structural stability.
[0029] In the related art, the ternary positive electrode material for high voltage is usually made into a single crystal or a quasi-single crystal morphology similar to the morphology of lithium cobalt oxide to improve the above problems, but the process is difficult, the rebound is serious after the pole piece is made, and the capacity and rate performance are low; there are also secondary spherical ternary materials provided by the related art, which have poor cycle performance under high voltage due to low resistance to electrolyte corrosion and stress erosion under high voltage. For example, in some embodiments, a porous conductive polyimide material containing an imidazole structure is composited with a lithium ion positive electrode material, and a porogen and a conductive filler are uniformly dispersed in an organic solvent. Under the protection of an inert atmosphere, a diamine monomer containing an imidazole structure is dissolved in an organic solvent, and then a dianhydride monomer is added in batches to mix the solution uniformly for polymerization to obtain a porous conductive polyamic acid (PAA) dispersion containing an imidazole structure, which is then composited with a lithium ion positive electrode material to form a positive electrode material; however, the use of an organic porogen to form a porous structure in polyimide has problems such as uneven dispersion of the organic porogen and inability to effectively remove the porogen, and the process is complicated.
[0030] The present invention provides a method for preparing a coated nickel cobalt lithium manganese oxide positive electrode material, comprising:
[0031] Mixing a substrate with an inorganic coating agent to obtain a prefabricated substrate, wherein the substrate includes secondary spherical lithium nickel cobalt manganese oxide;
[0032] The polyamide is mixed with a first solvent, swelled and dissolved, and then mixed with a second solvent to obtain a polyamide solution, wherein the solubility of the polyamide in the first solvent is greater than that in the second solvent;
[0033] The polyamide solution is sprayed on the prefabricated substrate in an atomized form, and the solvent is removed, washed, centrifuged, and dried to obtain a coated nickel-cobalt-manganese-oxide lithium positive electrode material.
[0034] The substrate is mixed with an inorganic coating agent to obtain a prefabricated substrate, wherein the substrate includes secondary spherical nickel cobalt manganese oxide; polyamide is mixed with a first solvent, swelled and dissolved, and then mixed with a second solvent to obtain a polyamide solution; the polyamide solution is sprayed on the prefabricated substrate in an atomized manner, the solvent is removed, washed, centrifuged, and dried. By volatilizing the solvent, polyamide is precipitated to form a porous film attached to the surface of the nickel cobalt manganese oxide substrate, and a polyamide porous film can be formed to coat the nickel cobalt manganese oxide substrate to improve the cycle performance of the prepared positive electrode material under high voltage, and the prepared positive electrode material can improve the structural stability and resist electrolyte corrosion under high voltage. Moreover, the preparation method of the present invention can make the solvent evenly dispersed, and can ensure that the solvent can be reliably removed, and the process is simple and easy to control.
[0035] The positive electrode material prepared by the preparation method of the present invention has an organic-inorganic coating layer formed on its surface, which improves the cycle performance of the material under high voltage. The nickel cobalt manganese oxide matrix is coated with a polyamide porous membrane, which can resist electrolyte corrosion under high voltage conditions, avoid direct contact between the positive electrode material and the electrolyte, and is conducive to the repeated release and embedding of lithium.
[0036] Optionally, the secondary spherical nickel-cobalt-lithium manganese oxide ternary material as a matrix may also be doped with aluminum (Al), yttrium (Y), indium (In), and the like.
[0037] In a preferred embodiment, the inorganic capping agent is nanoparticles having conductive properties.
[0038] Furthermore, the nanoparticles having conductive properties include silane-modified conductive zinc oxide whiskers.
[0039] Optionally, the silane in the silane modification may be 3-aminopropyltriethoxysilane or the like.
[0040] It should be noted that the silane-modified conductive zinc oxide whiskers embedded in the matrix and the polyurethane coating film can enhance the toughness and strength of the material, so that the positive electrode sheet made of the positive electrode material has good bending resistance, thereby improving the serious rebound problem of the positive electrode sheet, and the preparation process is simple and easy to operate.
[0041] In a preferred embodiment, the inorganic coating agent accounts for 1%-10% of the weight of the substrate, for example: 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., which are not specifically limited here.
[0042] In the present invention, the first solvent is selected from at least one of formamide, glycerol and ethylene glycol.
[0043] In the present invention, the second solvent is selected from at least one of formamide, glycerol and ethylene glycol.
[0044] It should be noted that the solubility of polyamide in the first solvent is greater than the solubility of polyamide in the second solvent; the solubilities of formamide, glycerol and ethylene glycol decrease in sequence, so when selecting the first solvent and the second solvent, they should be selected according to the above requirements, for example: when the first solvent is formamide, the second solvent includes at least one of glycerol and ethylene glycol; when the first solvent is glycerol, the second solvent includes at least ethylene glycol; no specific limitation is made here.
[0045] In a preferred embodiment, the ratio of the mass of the polyamide to the total mass of the first solvent and the second solvent is 1%-5%, for example: 1%, 2%, 3%, 4%, 5%, etc.
[0046] Furthermore, the mass ratio of the first solvent to the second solvent is (3-8):(4-6), for example: 3:4, 4:3, 3:5, 3:6, 1:1, 4:5, 2:3, 5:4, 5:6, 3:2, 6:5, 7:4, 7:5, 7:6, 2:1, 8:5, etc., which is not specifically limited here.
[0047] In a preferred embodiment, the polyamide is a polyamide oligomer having a weight average molecular weight Mw of 1000-50000 g / mol, for example 1000 g / mol, 5000 g / mol, 10000 g / mol, 20000 g / mol, 25000 g / mol, 30000 g / mol, 40000 g / mol, 50000 g / mol, etc.
[0048] Furthermore, the mass ratio of the polyamide solution to the prefabricated matrix is 2:(2-4), for example: 1:1, 2:3, 1:2, etc.
[0049] In a preferred embodiment, the method for removing the solvent includes heat treatment, and the heat treatment temperature is 120°C-180°C, for example: 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc.
[0050] During the heat treatment process, due to the difference in solvents, the solubility of polyamide in the first solvent is better than that in the second solvent. The volatilization of the solvent and the solubility of polyamide are regulated at different temperatures. After the solvent evaporates, the polyamide precipitates to form a porous film attached to the surface of the substrate; at the same time, the terminal amine group of the polyamide and the silane bond in the silane-modified conductive zinc oxide whisker form intermolecular forces and hydrogen bridge bonds, bonding to form a network structure, thereby enhancing the bonding force between the polyamide film and the substrate, and enhancing the structural stability and conductive properties of the positive electrode material.
[0051] In some embodiments, the temperature for drying the coated lithium nickel cobalt manganese oxide positive electrode material may be 120-150°C.
[0052] The present invention is further described in detail below in conjunction with embodiments.
[0053] Example 1
[0054] S1: 10g secondary spherical nickel cobalt manganese oxide ternary material LiNi 0.9 Co 0.05 Mn 0.05 O2 is used as a matrix, and is placed in a mixing device together with 1g of silane-modified zinc oxide whiskers to be mixed evenly to obtain a prefabricated matrix.
[0055] S2: Add polyamide to the formamide solvent, stir to swell and dissolve, then add solvent glycerol, stir and mix thoroughly for 30 minutes to obtain a polyamide solution; wherein the mass ratio of formamide to glycerol is 3:4, and the ratio of the mass of polyamide to the total mass of formamide and glycerol is 1%.
[0056] S3: The polyamide solution is sprayed into the mixing device by rotary atomization, and then mixed with the prefabricated substrate, and heat-treated at 120°C and 180°C in turn to remove the solvent, forming a polyamide porous membrane and coating the surface of the substrate, washing, centrifuging, and then drying at 120°C to form a coated nickel cobalt manganese oxide lithium positive electrode material; SEM image is shown in Figure 1 .
[0057] from Figure 1 It can be seen that the preparation method of the present invention can prepare a polyamide porous membrane-coated lithium nickel cobalt manganese oxide matrix.
[0058] Example 2
[0059] S1: Secondary spherical nickel cobalt manganese oxide ternary material LiNi 0.9 Co 0.05 Mn 0.05 O2 is used as a matrix, and is placed in a mixing device together with silane-modified zinc oxide whiskers to be mixed evenly to obtain a prefabricated matrix; the silane-modified zinc oxide whiskers account for 1% of the weight of the matrix.
[0060] S2: Add polyamide to glycerol solvent, stir to swell and dissolve, then add a mixed solvent of formamide and ethylene glycol, stir and mix thoroughly for 30 minutes to obtain a polyamide solution; wherein the ratio of polyamide to the total mass of glycerol, formamide and ethylene glycol is 3%, and the ratio of glycerol to the total mass of formamide and ethylene glycol is 4:3.
[0061] S3: The polyamide solution is rotary atomized and sprayed into a mixing device, and then mixed with the prefabricated substrate, and heat-treated at 130°C and 160°C in turn to remove the solvent, forming a polyamide porous membrane and coating the surface of the substrate, washing, centrifuging, and then drying at 120°C to form a coated nickel cobalt manganese oxide lithium positive electrode material.
[0062] Example 3
[0063] S1: Secondary spherical nickel cobalt manganese oxide ternary material LiNi 0.9 Co 0.05 Mn 0.05 O2 is used as a matrix, and is placed in a mixing device together with silane-modified zinc oxide whiskers for uniform mixing to obtain a prefabricated matrix; the silane-modified zinc oxide whiskers account for 5% of the matrix.
[0064] S2: Add polyamide to a mixed solvent of formamide and glycerol, stir to swell and dissolve, then add solvent ethylene glycol, stir and mix thoroughly for 30 minutes to obtain a polyamide solution; wherein the ratio of the total mass of polyamide to glycerol, formamide and ethylene glycol is 1%, and the mass ratio of the total mass of formamide and glycerol to ethylene glycol is 1:2.
[0065] S3: The polyamide solution is rotary atomized and sprayed into a mixing device, and then mixed with the prefabricated substrate, and heat-treated at 140°C and 150°C in sequence to remove the solvent, forming a polyamide porous membrane and coating the surface of the substrate, washing, centrifuging, and then drying at 120°C to form a coated nickel cobalt manganese oxide lithium positive electrode material.
[0066] Example 4
[0067] S1: Secondary spherical nickel cobalt manganese oxide ternary material LiNi 0.9 Co 0.05 Mn 0.05 O2 is used as a matrix, and is placed in a mixing device together with silane-modified zinc oxide whiskers to be mixed evenly to obtain a prefabricated matrix; the silane-modified zinc oxide whiskers account for 3% of the matrix.
[0068] S2: adding polyamide to formamide solvent, stirring to swell and dissolve, then adding ethylene glycol, stirring and mixing thoroughly for 30 minutes to obtain a polyamide solution; wherein the ratio of the total mass of polyamide to formamide and ethylene glycol is 2%, and the mass ratio of formamide to ethylene glycol is 2:1.
[0069] S3: The polyamide solution is rotary atomized and sprayed into a mixing device, and then mixed with the prefabricated substrate, and heat-treated at 120°C and 150°C in turn to remove the solvent, forming a polyamide porous membrane and coating the surface of the substrate, washing, centrifuging, and then drying at 120°C to form a coated nickel cobalt manganese oxide lithium positive electrode material.
[0070] Comparative Example 1
[0071] The difference between Comparative Example 1 and Example 1 is that in step S1, only the secondary spherical lithium nickel cobalt manganese oxide ternary material LiNi 0.9 Co 0.05 Mn 0.05 O2 is used as the matrix, no silane-modified zinc oxide whiskers are added, that is, no inorganic coating agent is added, and only polyamide forms a porous film to coat the surface of the lithium nickel cobalt manganese oxide matrix.
[0072] The material prepared in Comparative Example 1 has poor conductivity and stability.
[0073] Comparative Example 2
[0074] The difference between Comparative Example 2 and Example 1 is that the secondary spherical nickel-cobalt-manganese-oxide ternary material LiNi 0.9 Co 0.05Mn 0.05 O2 is the positive electrode material and is not subjected to any coating treatment as in Example 1.
[0075] The material prepared in Comparative Example 2 has poor conductivity and stability.
[0076] Comparative Example 3
[0077] The difference between Comparative Example 3 and Example 1 is that the secondary spherical nickel-cobalt-manganese-oxide ternary material LiNi 0.9 Co 0.05 Mn 0.05 O2 is used as a matrix, a silane-modified zinc oxide whisker inorganic coating agent is added, and polyamide is not used to form a porous film coated on the surface of the nickel cobalt manganese oxide lithium matrix.
[0078] The material prepared in Comparative Example 3 has poor conductivity and stability.
[0079] The resistivity of the positive electrode materials obtained in the embodiment and the comparative example was tested by a four-probe method at 12 MPa; the results are shown in Table 1.
[0080] Table 1
[0081] Resistivity (Ω·m) Example 1 1368 Example 2 1443 Example 3 1621 Comparative Example 1 6883 Comparative Example 2 7211 Comparative Example 3 6880
[0082] Test example
[0083] The positive electrode materials prepared in Example 1, Comparative Examples 1 and 2 were prepared into button cells for electrochemical performance test of lithium ion batteries, and the specific steps were as follows: using N-methylpyrrolidone as solvent, the positive electrode material was mixed with acetylene black and PVDF in a mass ratio of 9.2:0.5:0.3, coated on aluminum foil, dried at 80°C with air blast for 8 hours, and then vacuum dried at 120°C for 12 hours. The battery was assembled in an argon-protected glove box, the negative electrode was a metal lithium sheet, the diaphragm was a polypropylene film, the electrolyte was 1M LiPF6-EC / DMC (1:1, v / v), and a 2032-type button cell shell was used to assemble the button cell in an argon-protected glove box, and then the electrochemical performance test was carried out at 25°C at 3.0-4.2V. The results are shown in Table 2.
[0084] Table 2
[0085]
[0086]
[0087] According to the results in the above table, it can be seen that the positive electrode material prepared by the method provided by the present invention has better cycle performance after being prepared into a battery.
[0088] In summary, the preparation material of the coated nickel cobalt manganese oxide positive electrode material of the present invention is a nickel cobalt manganese oxide positive electrode material coated with a polyamide porous membrane, which resists electrolyte corrosion under high voltage conditions, avoids direct contact between the positive electrode material and the electrolyte, and is conducive to the repeated removal and embedding of lithium.
[0089] During the heat treatment process, due to the difference in solvents, that is, the solubility of polyamide in the first solvent is better than that in the second solvent, the volatilization of the solvent and the solubility of polyamide are regulated at different temperatures. After the solvent evaporates, the polyamide precipitates to form a porous film attached to the surface of the substrate; at the same time, the terminal amine group of the polyamide and the silane bond in the silane-modified conductive zinc oxide whisker form intermolecular forces and hydrogen bridge bonds, bonding to form a network structure, thereby enhancing the bonding force between the polyamide film and the substrate, and enhancing the structural stability and conductive properties of the positive electrode material.
[0090] The present invention forms an organic-inorganic coating layer on the surface of the positive electrode material to improve the cycle performance of the material under high voltage. Silane-modified conductive zinc oxide whiskers are embedded in the matrix and the polyurethane coating film to enhance the toughness and strength of the material. The positive electrode material is made into a positive electrode sheet with good bending resistance, which can solve the problem of severe springback of the positive electrode sheet, and the preparation process is simple.
[0091] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a coated nickel cobalt manganese oxide positive electrode material, characterized in that: include: Mixing a substrate with an inorganic coating agent to obtain a prefabricated substrate, wherein the substrate comprises secondary spherical lithium nickel cobalt manganese oxide; Mixing polyamide and a first solvent, dissolving, and then mixing with a second solvent to obtain a polyamide solution, wherein the solubility of the polyamide in the first solvent is greater than the solubility of the polyamide in the second solvent; Spraying the polyamide solution onto the surface of the prefabricated substrate, removing the solvent, washing, centrifuging, and drying to obtain the coated nickel cobalt manganese oxide lithium positive electrode material; The inorganic coating agent is conductive nanoparticles; the conductive nanoparticles include silane-modified conductive zinc oxide whiskers.
2. The method for preparing the coated nickel cobalt lithium manganese oxide positive electrode material according to claim 1, characterized in that: At least one of the first solvent and the second solvent is selected from at least one of formamide, glycerol, and ethylene glycol.
3. The method for preparing the coated nickel cobalt lithium manganese oxide positive electrode material according to claim 2, characterized in that: The ratio of the mass of the polyamide to the total mass of the first solvent and the second solvent is 1%-5%; the mass ratio of the first solvent to the second solvent is (3-8):(4-6).
4. The method for preparing the coated nickel cobalt lithium manganese oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The solvent removal comprises heat treatment, and the temperature of the heat treatment is 120-180°C.
5. The method for preparing the coated nickel cobalt lithium manganese oxide positive electrode material according to claim 1, characterized in that: The inorganic coating agent accounts for 1%-10% of the weight of the substrate.
6. The method for preparing the coated nickel cobalt lithium manganese oxide positive electrode material according to claim 1, characterized in that: The polyamide is a polyamide oligomer, and has a weight average molecular weight Mw of 1000-50000 g / mol.
7. The method for preparing the coated nickel cobalt lithium manganese oxide positive electrode material according to claim 1 or 6, characterized in that: The mass ratio of the polyamide solution to the prefabricated matrix is 2:(2-4).
8. A positive electrode material, characterized in that The positive electrode material is prepared by the method for preparing the coated nickel cobalt lithium manganese oxide positive electrode material according to any one of claims 1 to 7.
9. A battery, characterized in that: Comprising the positive electrode material as claimed in claim 8.
Citation Information
Patent Citations
Lithium ion battery high-voltage lithium-rich manganese-based positive electrode material coated with polyamide organic matter layer and coating and modifying method and application of material
CN109286013A
Doped and coated co-modified nickel cobalt lithium manganate positive electrode material and preparation method thereof
CN110911677A